Encyclopedia of China : the essential reference to China, its history and culture - Perkins, Dorothy (Facts on File, 1999)
More than 1,000 entries explore all aspects of China's past, present and future, with essay-length entries on provinces and major cities; Buddhism, Confucianism, Taoism and other religions; family life; calligraphy, embroidery, sculpture and other arts and crafts; folktales and mythology; martial arts, including tai chi chuan and kung fu; native animals and plants; emperors and dynasties; political movements and institutions; traditional medicine; contemporary leaders; festivals and holidays; foreign relations; language and writing; educational systems; Chinese communities around the world; and much more. Photographs and illustrations depict Chinese art and architecture, everyday life, cities, and political figures. An extensive system of cross-references link concepts, people and events.